Clinical pharmacokinetics of pramipexole, ropinirole and rotigotine in patients with Parkinson's disease. (April 2019) - Contin, Manuela; Lopane, Giovanna; Mohamed, Susan; Calandra-Buonaura, Giovanna; Capellari, Sabina; De Massis, Patrizia; Nassetti, Stefania; Perrone, Alessandro; Riva, Roberto; Sambati, Luisa; Scaglione, Cesa; Cortelli, Pietro
Abstract: Introduction: Pramipexole (PRA), ropinirole (ROP) and rotigotine (ROT) are non-ergoline dopaminergic agonists (DAs) used to treat Parkinson's disease (PD). Clinical pharmacokinetics of DAs is poorly characterized in PD. The main purpose of our study was to investigate the effect of dose, age and sex on steady-state plasma concentrations of DAs in real life PD patients on chronic DAs therapy. Methods: The study was single center, open and prospective. Blood samples for measurement of DAs plasma concentrations were drawn in the morning, at a median 18-h distance from the last DA dose. Results: Ninety-one patients treated with PRA, 50 with ROP and 37 with ROT were enrolled in the study. Plasma concentration of DAs significantly correlated with weight-adjusted daily dose in all subgroups, although at a given dose, matched plasma concentrations highly varied among patients. Median PRA plasma concentration-to-daily dose ratio (C/D) [(ng/mL)/(mg/kg/d)] was 68% higher in patients >65 years than ≤65 years (158 vs 94, p < 0.001), while was not affected by age in ROP and ROT subgroups. No sex-mediated differences in C/D ratios were observed in any group. Conclusion: These are the first observations on DAs pharmacokinetics in PD patients' everyday clinical practice. Of relevance, patients over 65yrs may require about one third of PRA dose compared to under 65yrs to achieve the same plasma concentration. Due to the high intersubject variability in plasma concentrations at the same dosage, we speculate that monitoring of plasma DAs might be helpful in the individualization of treatment in selected patients. Highlights: Dopamine agonists morning plasma concentrations proportional to daily dose in mg/kg. Older age increased plasma concentrations of pramipexole but not the other agonists. Sex did not affect morning plasma concentrations of dopamine agonists. Dopamine agonists adverse effects not associated with morning plasma concentrations.